Work Discipline Tops DBL Academy Staff Performance Model: Disiplin Kerja Menjadi Prioritas Utama dalam Model Kinerja Staf DBL Academy - Valencia, Aisa Renata; Fauziah, Sumainah (Academia Open, 2026)
General Background: Employee performance is shaped by organizational behavior factors that affect task completion, productivity, and workplace outcomes. Specific Background: DBL Academy Surabaya operates in the sports development sector, where intensive work demands require attention to work-life balance, work discipline, and work stress. Knowledge Gap: The study addresses the need to determine whether these three factors simultaneously and partially explain employee performance within the DBL Academy Surabaya context. Aims: This study aims to analyze the influence of work-life balance, work discipline, and work stress on employee performance at DBL Academy Surabaya. Results: Using an associative quantitative approach, questionnaires were distributed to all 70 employees through saturated sampling. Multiple linear regression with SPSS, t-tests, and F-tests at a 95% significance level showed that work-life balance, work discipline, and work stress simultaneously had a significant influence on employee performance, with F-count 6.081 greater than F-table 2.74 and significance 0.001. Partially, work-life balance was positive and significant with t 2.873 and significance 0.005, while work discipline was positive and significant with t 2.557 and significance 0.013. Work stress was not significant, with t 0.050 and significance 0.960. Novelty: The study provides census-based evidence on employee performance predictors in the DBL Academy Surabaya organizational setting. Implications: The findings indicate that stronger work-life balance and discipline are relevant managerial priorities, while work stress was not the main factor in this model. Highlights: Life-role balance showed positive and significant partial results. Job stress was not statistically significant in the partial test. The simultaneous test supported the combined role of all three predictors. Keywords: Work Life Balance, Work Discipline, Work Stress, Employee Performance